Elementary Principalas Technology Leadership Dispositions (Global Journal of Human-Social Science, 2015)
This qualitative study examined the reported technology dispositions that a group of elementary principals in a South Texas public school district possess as technology leaders as aligned to the 2009 National Technology Standards for Administrators (NETS-A). An online questionnaire and open-ended audio recorded interviews were utilized to determine technology dispositions of the participants. Findings included the following five dispositions: 1) Technology's usefulness, 2) Risk taking, 3) Self-reliance, 4) Encouragement, and 5) Role model.